Membaca Tubuh-Tubuh Patuh: Representasi Penciptaan Identitas Pribumi Melalui Tubuh-Tubuh Patuh di Hindia Belanda dalam Film Moeder Dao De Schildlapegelijkende - Ajeng Dewanthi (Lembaran Sejarah, 2019)
In the early twentith century, the Dutch colonial government launched a development program designated towards the modern Western world in the Dutch East Indies. This is due to the penetration of capital from Europe. In this process, they embraced the natives as part of the new world. The colonial authority used certain knowledge discourse systems that worked in various modern colonial institutions, such as offices, schools, religious institutions, mining, transportation, factories. In other words, the natives who originally had different knowledge from the colonists were subtly made to follow the logic of the colonial authorities. This paper will show various representations in the film Moeder Dao de Schildpadgelijkende, about how the practice of Western colonialism discourse in the Dutch East Indies during trying to internalization their knowledge system into the Indigenous knowledge system.Discourse is a disciplinary technology through the practice of certain knowledge to create docile bodies through a certain normalization process. In this process, a person acts treated in such a way is to enter into the system of knowledge pressed by the authorities. The indigenous body becomes the working locus of colonialism’s power and knowledge. A docile body exists a form of certain norms and rules in society. In this knowledge building, the logic of the colonial language as a tool for the formation of indigenous identities. The tangibility of inferiority created in the naratives arose from the perspective of the colonial rulers towards natives living in Western standards. Although the native people could meet Western standards, under the discourse of colonialism, it was still a subject that had to follow the colonial power itself.